2022
DOI: 10.3390/microorganisms11010059
|View full text |Cite
|
Sign up to set email alerts
|

A Lipopolysaccharide Synthesis Gene rfaD from Mesorhizobium huakuii Is Involved in Nodule Development and Symbiotic Nitrogen Fixation

Abstract: Rhizobium lipopolysaccharide (LPS) is an important component of the cell wall of gram-negative bacteria and serves as a signal molecule on the surface of rhizobia, participating in the symbiosis during rhizobia–legume interaction. In this study, we constructed a deletion mutant of ADP-L-glycerol-D-mannoheptosyl-6-exoisomerase (rfaD) of Mesorhizobium huakuii 7653R and a functional complementary strain. The results showed that the deletion of rfaD did not affect the free-living growth rate of 7653R, but that it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…5F ). Genes involved in lipopolysaccharide (LPS) biosynthesis and symbiosis, such as rafD and rafE ( 32 ), also are among the downregulated DEGs ( Fig. 5D ).…”
Section: Resultsmentioning
confidence: 99%
“…5F ). Genes involved in lipopolysaccharide (LPS) biosynthesis and symbiosis, such as rafD and rafE ( 32 ), also are among the downregulated DEGs ( Fig. 5D ).…”
Section: Resultsmentioning
confidence: 99%
“…5C ). Genes involved in lipopolysaccharide (LPS) biosynthesis and symbiosis, such as rafD and rafE (30), also are among the down-regulated DEGs ( Fig. 5B ).…”
Section: Resultsmentioning
confidence: 99%
“…Impairment of pa4067/oprG Possibly Linked to the Altered Morphology of ∆pa0665/pTS-pa0665 Mutant at 42 • C Transcriptomic analyses revealed that pa3337/rfaD and pa4067/oprG were among the top seven significantly downregulated genes (Figure 6C), both critical for the structural integrity of the bacterial outer membrane. oprG plays a key role in forming outer membrane channels in Gram-negative bacteria, crucial for molecular transport and affecting bacterial virility and antibiotic resistance [24], while rfaD is vital for lipopolysaccharide (LPS) biosynthesis, a key outer membrane component in Gram-negative bacteria [25,26]. To investigate the impact of disrupting pa3337/rfaD and pa4067/oprG on cellular morphology, we constructed knockout plasmids containing sequences approximately 500 bp identical to the N-terminal coding sequences of pa3337/rfaD and pa4067/oprG.…”
Section: Transcriptomic Analysis Reveals Impaired Oxidative Phosphory...mentioning
confidence: 99%